PELATIHAN PEMBUATAN ECOPRINT PADA IBU-IBU PKK DI KELURAHAN GUNUNGPATI KOTA SEMARANG - Sholikhah, Roudlotus; Widowati, Widowati; Nurmasitah, Sita (Department of Home Economics, Faculty of Engineering, Universitas Negeri Semarang, 2021)
Abstract. This service aims to provide training on making Ecoprints for PKK women in the Kalisegoro Gunungpati village which has the potential to increase the creative industry with products that have economic value and are worth selling. The methods implemented in this community service are: (1) providing theoretical material about making Ecoprints and entrepreneurship which will be delivered using lecture and discussion methods, (2) practical materials for making Ecoprints and entrepreneurship are given using demonstration methods, exercises and project-based learning, (3) monitoring and evaluation. The instrument used to measure the success of the training is a product assessment sheet. The training activities made the Ecoprint of housewives in Gunungpati Village to be carried out properly and smoothly. The implementation of the training makes the Ecoprint can be carried out according to the plan, all the planned materials can be carried out properly. There has been an increase in understanding from 40% to 80% of materials regarding Ecoprint. The results of the evaluation of the Ecoprint making training in Kalisogoro Gunungpati Village, namely an increase in the understanding and ability of participants before and after being given training on making Ecoprints, among others, are as follows: 1) mastery of the use of tools and materials for making Ecoprints from 26% increased to 95%; 2) mastery of Ecoprint manufacturing techniques from 0% increased to 98%; 3) Ecoprint creation creativity increased from 0% to 93%; 4) Ecoprint product yield increased from 0% to 100%; 5) participant participation during Ecoprint training increased from 0% to 100%; and 6) understanding of entrepreneurship theory from 10% increased to 87%. Keywords: Training, Ecoprint, Gunungpati Village Abstrak. Pengabdian ini bertujuan untuk memberikan pelatihan membuat Ecoprint bagi ibu-ibu PKK di kelurahan Kalisegoro Gunungpati yang berpotensi untuk peningkatan industri kreatif dengan produk yang bernilai ekonomis dan layak jual. Metode yang dilaksanakan dalam pengabdian masyarakat ini adalah: (1) pemberian materi teori tentang membuat Ecoprint dan kewirausahaan yang akan disampaikan dengan metode ceramah dan diskusi, (2) materi praktek membuat Ecoprint dan kewirausahaan diberikan dengan metode demontrasi, latihan dan pembelajaran berbasis proyek, (3) monitoring dan evaluasi. Instrumen yang digunakan untuk mengukur keberhasilan pelatihan adalah lembar penilaian produk. Kegiatan pelatihan membuat Ecoprint ibu-ibu rumah tangga di Kelurahan Gunungpati dapat dilaksanakan dengan baik dan lancar. Pelaksanaan pelatihan membuat Ecoprint dapat terlaksana sesuai perencanaan, materi yang direncanakan dapat terlaksana semua dengan baik. Telah terjadi peningkatan pemahaman dari 40% menjadi 80% materi mengenai Ecoprint. Hasil evaluasi pelatihan pembuatan Ecoprint di Kelurahan Kalisogoro Gunungpati yaitu terjadi peningkatan pemahaman dan kemampuan peserta sebelum dan sesudah diberikan pelatihan pembuatan Ecoprint antara lain sebagai berikut: 1) penguasaan terhadap penggunaan alat dan bahan pembuatan Ecoprint dari 26% meningkat menjadi 95%; 2) penguasaan teknik pembuatan Ecoprint dari 0% meningkat menjadi 98%; 3) kreativitas pembuatan Ecoprint dari 0% meningkat menjadi 93%; 4) hasil produk Ecoprint dari 0% meningkat menjadi 100%; 5) partisipasi peserta selama pelatihan Ecoprint dari 0% meningkat menjadi 100%; dan 6) pemahaman teori kewirausahaan dari 10% meningkat menjadi 87%. Kata Kunci: Pelatihan, Ecoprint, Kelurahan Gunungpati